There is a sequence $x_n$ defined recursively:

$$x_{n+2} = \frac{x_n + x_{n+1}}{2}, n\geqslant1 $$

And $x_1=a$, $x_2=b$.

I need to find $lim_{n\to\infty} x_n$.

First, I decieded to get rid of recurrent definition, and I got the following:

$$x_n=a+\sum_{k=1}^{n}\frac{b-a}{2^k} = a+(b-a)\sum_{k=1}^{n}\frac{1}{2^k}$$

And then I started finding the limit:

$$lim_{n\to\infty} x_n = a + (b-a) (lim_{n\to\infty}\sum_{k=1}^{n}\frac{1}{2^k})$$

As long as $\sum_{k=1}^{inf}\frac{1}{2^k}$ is 1, it equals to $a+(b - a)$ which is $b$. But this answer is marked as wrong.

What is my mistake?

  • 2
    $\begingroup$ The closed form of $x_n$ is $x_n =(\dfrac{a+b}{3})(1-(-0.5)^{n-2})+\dfrac{b}{3}(1-(-0.5)^{n-3})$ $\endgroup$ – Aryaman Jal Dec 2 '17 at 12:37

Consider substitution $x_n = \xi^n$. Recurrent definition says now that $$2\xi^2 = 1 + \xi.$$

Arbitrary solution to second order recurrent equation is a linear combination of $\xi_{1,2}$. But we have two initial conditions $x_1 =a$ and $x_2 = b$.

PS. Concerning your solution. I think it doesn't satisfy the recurrent equation. Probably you should check it.


rearrange $x_{n+2} = \frac{x_n + x_{n+1}}{2}$ into $x_{n}=\frac12x_{n-1}+\frac12x_{n-2}$, you can see that this is a linear homogenous recurrence relation of degree $2$. in this case let's solve it by saying $x_n=r^n$ thus $x_{n}=\frac12x_{n-1}+\frac12x_{n-2}\implies r^n=\frac12r^{n-1}+\frac12r^{n-2}\implies r^2=\frac12r^1+\frac12\implies r_{1,2}=\begin{cases}1\\-\frac12\end{cases}$

with this we can get to the equation $x_n=c_1\cdot1^n+c_2\cdot\left(-\frac12\right)^n=c_1+c_2\cdot\left(-\frac12\right)^n$ and with the initial condition we have $x_1=c_1-\frac12c_2=a$ and $x_2=c_1+\frac14c_2=b$ solve this:$$c_1=a+\frac12c_2\implies c_1+\frac14c_2=a+\frac12c_2+\frac14c_2=a+\frac34c_2=b\implies c_2=\frac43\left(b-a\right)\\\implies c_1=a+\frac12\cdot\frac43\left(b-a\right)=a+\frac23\left(b-a\right)$$


Now that I think about it you don't even need to find $c_2$, because $\lim_{n\to\infty}(-1/2)^n=0$ you have $\lim_{n\to\infty}x_n=c_1$. So instead of what I did you should solve for $c_1$ first and then you can stop.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.